Effects of ursolic acid on the structural and morphological behaviours of dipalmitoyl lecithin vesicles - Lőrincz, András; Mihály, Judith; Németh, Csaba; András Wacha; Bóta, Attila (Biochimica et Biophysica Acta (BBA) - Biomembranes, 2015)
Effects of ursolic acid on the structural and morphological characteristics of dipalmitoyl lecithin(DPPC)-water system was studied by using differential scanning calorimetry (DSC), small- and wide-angle X-ray scattering (SWAXS), freeze-fracture method combined with transmission electron-microscopy (FF-TEM) and infrared spectroscopy (FT-IR). The surface of the uncorrelated lipid system is rippled or grained and a huge number of small, presumably unilamellar vesicles are present if the UA/DPPC molar ratio is 0.1 mol/mol or higher. Besides the destroyed layer packing of regular multilamellar vesicles, non-bilayer (e.g. cubic or hexagonal) local structures are evidenced by SAXS and FF-TEM methods. The ability of UA to induce non-bilayer structures in hydrated DPPC system originates from the actual geometry form of associated lipid and UA molecules as concluded from the FT-IR measurements and theoretical calculations. Beside numerous beneficial e.g. chemopreventive and chemotherapeutic effect of ursolic acid against cancer, their impact to modify the lipid bilayers can be utilized in liposomal formulations.
Keywords: DPPC; Freeze-fractured transmission electron-microscopy (FF-TEM); Kratky camera; Non-bilayer lipid structure; peer-reviewed; Small- and wide-angle X-ray scattering (SWAXS); Ursolic acid

Physicochemical characterization of artificial nanoerythrosomes derived from erythrocyte ghost membranes - Deák, Róbert; Mihály, Judith; Szigyártó, Imola Cs.; András Wacha; Lelkes, Gábor; Bóta, Attila (Colloids and Surfaces B: Biointerfaces, 2015)
Colloidal stabile nanoerythrosomes with 200 nm average diameter were formed from hemoglobin-free erythrocyte ghost membrane via sonication and membrane extrusion. The incorporation of extra lipid (1,2-dipalmitoyl-sn-glycero-3-phosphocholine, DPPC), added to the sonicated ghosts, caused significant changes in the thermotropic character of the original membranes. As a result of the increased DPPC ratio the chain melting of the hydrated DPPC system and the characteristic small angle X-ray scattering (SAXS) of the lipid bilayers appeared. Significant morphological changes were followed by transmission electron microscopy combined with freeze fracture method (FF-TEM). After the ultrasonic treatment the large entities of erythrocyte ghosts transformed into nearly spherical nanoerythrosomes with diameters between 100 and 300 nm and at the same time a great number of 10–30 nm large membrane proteins or protein clusters were dispersed in the aqueous medium. The infrared spectroscopy (FT-IR) pointed out, that the sonication did not cause changes in the secondary structures of the membrane proteins under our preparation conditions. About fivefold of extra lipid – compared to the lipid content of the original membrane – caused homogeneous dispersion of nanoerythrosomes however the shape of the vesicles was not uniform. After the addition of about tenfold of DPPC, monoform and monodisperse nanoerythrosomes became typical. The outer surfaces of these roughly spherical objects were frequently polygonal, consisting of a net of pentagons and hexagons.
Keywords: CREDO; Erythrocyte; Freeze fracture TEM; Infrared spectroscopy; Nanoerythrosomes; Protein to lipid ratio; Small angle X-ray scattering (SAXS); Vesicles

Mechanical Stability and Fibrinolytic Resistance of Clots Containing Fibrin, DNA, and Histones - Longstaff, Colin; Varjú, Imre; Sótonyi, Péter; Szabó, László; Krumrey, Michael; Hoell, Armin; Bóta, Attila; Varga, Zoltán; Komorowicz, Erzsébet; Kolev, Krasimir (Journal of Biological ChemistryJournal of Biological Chemistry, 2013)
Neutrophil extracellular traps are networks of DNA and associated proteins produced by nucleosome release from activated neutrophils in response to infection stimuli and have recently been identified as key mediators between innate immunity, inflammation, and hemostasis. The interaction of DNA and histones with a number of hemostatic factors has been shown to promote clotting and is associated with increased thrombosis, but little is known about the effects of DNA and histones on the regulation of fibrin stability and fibrinolysis. Here we demonstrate that the addition of histone-DNA complexes to fibrin results in thicker fibers (increase in median diameter from 84 to 123 nm according to scanning electron microscopy data) accompanied by improved stability and rigidity (the critical shear stress causing loss of fibrin viscosity increases from 150 to 376 Pa whereas the storage modulus of the gel increases from 62 to 82 pascals according to oscillation rheometric data). The effects of DNA and histones alone are subtle and suggest that histones affect clot structure whereas DNA changes the way clots are lysed. The combination of histones + DNA significantly prolongs clot lysis. Isothermal titration and confocal microscopy studies suggest that histones and DNA bind large fibrin degradation products with 191 and 136 nm dissociation constants, respectively, interactions that inhibit clot lysis. Heparin, which is known to interfere with the formation of neutrophil extracellular traps, appears to prolong lysis time at a concentration favoring ternary histone-DNA-heparin complex formation, and DNase effectively promotes clot lysis in combination with tissue plasminogen activator.
Keywords: DNA; Fibrinolysis; Histones; Neutrophil; Neutrophil Extracellular Trap; Tissue Plasminogen Activator (tPA)

X-ray Data Booklet - Attwood, David; Gullikson, Eric; Howells, Malcolm; Kim, Kwang-Je; Kirz, Janos; Kortright, Jeffrey; Lindau, Ingolf; Liu, Yanwei; Pianetta, Piero; Robinson, Arthur; Scofield, James; Underwood, James; et al. (Lawrence Berkeley National Laboratory, University of California, 2009)